BRIO3 Bioregulatory infiltration therapy with ozone for musculoskeletal pain management, the experience with 229 cases (Ozone Therapy Global Journal, 2016)
Last decade was named the decade of the articulation and bone (1) according to a study by WHO  musculo skeletal injuries are the most frequent cause of chronic pain and disability worldwide.(2) Thus the importance of obtaining the most comprehensive treatment that will resolve the pain and restore the functional level to the patient. The mainstream treatment with the available resources of NSAIDs, muscle relaxants, or corticosteroids are effective in the management of the acute pain, but do not offer advantages in the regeneration of the damaged tissue, and can have side effects and risks in the areas of coagulation, gastric lesions of nephrotoxicity well documented. The use of nontraditional therapies such as the injection of medical ozone widens our medical arsenal and allows us to combine different alternative therapies to resolve the osteo articular pathology. The innovative technique of Prolozone , designed by Dr. Shallenberger, makes use a combination of agents(local anesthetic procaine, mixture or vitamins, dextrose, and very low dosage of corticosteroids) with medical grade ozone to apply subcutaneously, intramuscularly or perilesionally depending on the case; positive results are reported(3).